A Precarious Construct: The Commission As A Curatorial Mode Of Inquiry - Sørensen, Trine Friis (The Nordic Journal of Aesthetics, 2017)
This article turns on a curatorial project that Trine Friis Sørensen conducted in relation to the Danish Radio Archive (the DR Archive) by commissioning two artists, Kajsa Dahlberg and Olof Olsson, to engage with the archive and produce artworks in relation to it. Focusing on the practice of commissioning rather than its outcome, the article proposes to consider commissioning as a curatorial mode of inquiry into the DR Archive and in turn asks why we commission, how the commission works and what kind of thinking the commission engenders. Drawing on Bruno Latour, Michel Foucault and in particular Jacques Derrida, this thinking with and through the practice of commissioning eventually prompts